Primary School Teachers Perceptions toward Urgency of Interpersonal Relationships in Primary Schools - Ramadhanty, Evila; Hermanto, Hermanto; Fathoni, Anang (Jurnal Pendidikan Progresif, 2023)
Primary School Teachers Perceptions of the Urgency of Interpersonal Relationships in Primary Schools. This research study aims to (1) explore the experiences of primary school teachers in conducting interpersonal relationships in the world of education; (2) describe the problems in conducting interpersonal relationships among teachers. This research is qualitative research with a phenomenological type. Data were collected through interviews with participants of 11 primary school teachers. Data analysis was performed based on the Bogdan & Biklen analysis model which begins by looking for themes and sub-themes on the topics covered. Next look for relationships between sub-themes to get a conclusion. The results showed that good interpersonal relationships will make students more open, enthusiastic, and motivated when studying, feel comfortable in learning, and will try to show their best performance in class. Furthermore, although the teacher has tried to understand the learners with their interpersonal intelligence, there are still conflicts when interacting with some students in the classroom. So it can be concluded that interpersonal relationships are urgent for teachers in building positive relationships with students, to improve the quality of their learning in the classroom. Keywords: interpersonal relationships, primary school teacher, student, teacher student interaction, teacher perception.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202330